If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -49 = -2 Reorder the terms: -49 + y = -2 Solving -49 + y = -2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '49' to each side of the equation. -49 + 49 + y = -2 + 49 Combine like terms: -49 + 49 = 0 0 + y = -2 + 49 y = -2 + 49 Combine like terms: -2 + 49 = 47 y = 47 Simplifying y = 47
| 86-2x=6-10x | | 1/x^3=0 | | 0=x-4+3x | | 1/x^3 | | 2xy+3z+1=0 | | x-3-8x-6= | | 5x-2=13x-19 | | 5w^2-30w+40=0 | | 80-5x+4x+10+80=180 | | -6(4y)= | | 6u+6(u-6)=36 | | 4x+10+80-5x=180 | | 13d^2-7d=0 | | -x+17y=127 | | 4(2x-1)-(-3+7)= | | 2y+9=4y-3 | | -1-7x=36x+6(-7-x) | | 4x^4y-36x^3y+80x^2y= | | (17+a)+12= | | x+3=x+11 | | 3z=6z-1 | | 2(-1-3x)=25+3x | | 4M-2(M+6)=5(3M-2)+6 | | 4+4(4x-4)=8-3(2x+1) | | 2y+2=-3 | | 5a-2+3a=17+12a-23 | | x^2-8x+64= | | Y=4Y^2-32Y+65 | | 7(w-8)+7w=14 | | 2x+10+4x-20=180 | | 2t+2=11 | | 5Q-3+2Q=10+9Q-3 |